Dificultades de aprendizajes en el proceso de enseñanza - aprendizaje de los estudiantes de décimo año de educación básica del colegio Dr. Modesto Chávez Franco de la ciudad de Santa Rosa periodo lectivo 2014 - 2015. - Sócola Jaramillo, Keyner Elías (2015)
At present learning difficulties take on vital importance for education, in contrast to previous decades when the problem was derived professionals to address the problem and preventing especially some students with these problems interrupted formal education, relegating student to continue with a series of treatments and even experiments to try to understand their problem.